How to do it: investigate exertional rhabdomyolysis (or not). Issue 1 (10th October 2018) - Fernandes, Peter M; Davenport, Richard J
Abstract : Rhabdomyolysis is the combination of symptoms (myalgia, weakness and muscle swelling) and a substantial rise in serum creatine kinase (CK) >50 000 IU/L; there are many causes, but here we specifically address exertional rhabdomyolysis. The consequences of this condition can be severe, including acute kidney injury and requirement for higher level care with organ support. Most patients have 'physiological' exertional rhabdomyolysis with no underlying disease; they do not need investigation and should be advised to return to normal activities in a graded fashion. Rarely, exertional rhabdomyolysis may be the initial presentation of underlying muscle disease, and we review how to identify this much smaller group of patients, who do require investigation.